Passionate communities : reading lesbian resistance in Jane Rule's fiction - Schuster, Marilyn R. (Cutting edge (New York, N.Y.), 1999)
In this new full-length study of Jane Rule's life and work, Marilyn Schuster argues that Rule's novels provide a way of "writing and reading lesbian" that resists and subverts dominant discourses of gender and sexuality-both those of mainstream culture and of political and sexual subcultures. From her earliest novel, Desert of the Heart (1964), Rule's fiction has provided a challenge to the concept of a fixed identity and to the identity politics founded on such a concept. Incorporating all of Jane Rule's early work-including unpublished manuscripts, letters, magazine and newspaper columns, as well as fan mail she received-Schuster also draws on interviews, conversations, and personal encounters with the author to elicit the ways in which Rule interrogates the meanings and politics of sexuality, the relationship between sexuality and language, and the stakes of communities in individual claims on identity. Passionate Communities is a thorough, engaging, and long-overdue study of an important voice in lesbian literature and gay and lesbian politics